2020
DOI: 10.1186/s40359-020-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of prognostic genetic testing in uveal melanoma patients: a controlled prospective clinical observational study

Abstract: Background: The risk of metastases in uveal melanoma can accurately be estimated through genetic analysis of the tumor. A growing number of patients decide to receive information on their prognosis, although this can be extremely burdensome. Studies on the psychosocial impact of testing are sparse. The objective of this study was to examine traits of patients opting for prognostication, to investigate its psychosocial impact and the use of psychooncological services over time. We further examined characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…Previous UM studies [ 3 , 14 , 15 ] have generally not detected greater psychological harm associated with poor prognosis, although Hope-Stone et al [ 15 ] found higher depression scores. Our study was more highly powered, and it is likely that we detected a small effect that had been missed in previous smaller samples.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous UM studies [ 3 , 14 , 15 ] have generally not detected greater psychological harm associated with poor prognosis, although Hope-Stone et al [ 15 ] found higher depression scores. Our study was more highly powered, and it is likely that we detected a small effect that had been missed in previous smaller samples.…”
Section: Discussionmentioning
confidence: 97%
“…In a sample of 99 survivors, Beran et al [ 3 ] found no indication of greater depressive symptoms or lower QoL associated with a poor prognosis compared to a good prognosis. In 175 survivors with follow-up exceeding 12 months, Lieb et al [ 14 ] found that trends in distress and anxiety and depression symptoms did not differ between survivors with good and poor prognostic outcomes or those who declined testing. However, only 63 survivors accepted testing.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing their fate could have signi cant implications for patients in terms of their psychological state and future life planning [8][9][10]. Some authors state that this information could be burdensome to patients and may be re ected in higher scores for depression, higher distress, and lower quality of life in patients with monosomy 3, as reported by Hope-Stones et al and Reimer et al [11,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found the test results to have no or little impact on anxiety and depression, and largely show mental QOL comparable to that of an agematched healthy norm population [8,13]. Lieb et al prospectively investigated 63 patients opting for CGT and showed that the perceived risk of developing metastasis increased in patients after receiving a poor prognosis and decreased in patients with good prognosis [10]. However, the same study observed that anxiety, depression, general distress, and fear of progression declined equally in all patients after primary treatment, regardless of their prognosis or their decision about undergoing CGT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation